Persepsi khalayak terhadap kredibiliti media di Malaysia - Normah Mustaffa,; Faridah Ibrahim,; Mus Chairil Samani,; Mohd. Helmi Abd. Rahim, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2010)
This article analyses the credibility component of news in newspapers, television and online. This study intends to seek public’s perception on news credibility in newspaper, television and Internet. Survey method on 100 respondents in Klang Valley were carried out in 2009 to assess newspaper news credibility, television and online by using news credibility scale as proposed by Gaziano and McGrath (1986) namely trust, currency, bias, fair, complete, objective, honest, latest, believe/confident, balanced, accuracy and on time. The finding shows that news credibility in newspaper and television have similarity but not for news credibility on Internet